A spinning method for low-torsion composite yarn with basalt fibers and staple cotton fibers - Li, Wei; Peng, Zhiyong; Zhang, Ruicheng; Wang, Xin; Li, Juan; Sun, Yue; Xu, Weilin; Xu, Duo; Liu, Keshuai (Frontiers in Materials, 2023)
Basalt fibers play an indispensable role in aerospace as well as fireproof suits in specialty fields. However, basalt fibers usually have properties such as high temperature and corrosion resistance, severely lack comfort, and are prone to brittle fracture or splitting when subjected to bending or impact forces because of their high modulus. Although considerable efforts have been made to solve the above problems by wrapping soft staple fibers with basalt, but the problem of difficult stress balance exists in the composite process. Herein, we demonstrate that a stress balance spinning method to control the composite conformation between high stiffness basalt fibers and soft cotton fibers, possess significant modulus differences, for high spinnability and comfort composite yarns production on ring spinning. Geometric analysis demonstrated that the stress during retwisting adjusts the internal structure of the basalt fiber and changes the arrangement of exposed cotton fiber bundles, causing the fiber motion track to change from concentric helix to deformed nonconcentric helix. The mechanical aspects show that over-twisted composite yarns lead to fiber exposure as well as detachment due to irregular fiber twisting, while low-twisted composite yarns can overcome residual torque and modulus differences. Afterwards, a systematic comparison of composite yarns with different parameters reveals that low-twisted composite yarns have a better helicoid structure, strength and uniformity than raw and over-twisted composite yarns.